2019
DOI: 10.3390/pharmaceutics11120669
|View full text |Cite
|
Sign up to set email alerts
|

Niosomal Formulation of a Lipoyl-Carnosine Derivative Targeting TRPA1 Channels in Brain

Abstract: The transient receptor potential akyrin type-1 (TRPA1) is a non-selective cation channel playing a pivotal role in pain sensation and neurogenic inflammation. TRPA1 channels expressed in the central nervous system (CNS) have a critical role in the modulation of cortical spreading depression (CSD), which is a key pathophysiological basis of migraine pain. ADM_09 is a recently developed lipoic acid-based TRPA1 antagonist that is able to revert oxaliplatin-induced neuropathic pain and inflammatory trigeminal allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…The particle size, polydispersion index (PDI), and ζ-potential of niosomes, freshly prepared and after reconstitution, are reported in Table S1. After reconstitution, raw niosomes (blank) and niosomes- 2 have a size below 150 nm in accordance with our previous work; thus, no effect was observed on the size of niosomes loaded with glycolipid 2 . Conversely, larger vesicles were obtained upon loading with glycolipid 7 .…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The particle size, polydispersion index (PDI), and ζ-potential of niosomes, freshly prepared and after reconstitution, are reported in Table S1. After reconstitution, raw niosomes (blank) and niosomes- 2 have a size below 150 nm in accordance with our previous work; thus, no effect was observed on the size of niosomes loaded with glycolipid 2 . Conversely, larger vesicles were obtained upon loading with glycolipid 7 .…”
Section: Resultssupporting
confidence: 90%
“…Niosomes were prepared using a thin-layer evaporation paddle, which was a partial modification of a previous method. , A detailed description of the niosomes’ preparation is provided in Supporting Information. The particle size, polydispersion index (PDI), and ζ-potential of niosomes, freshly prepared and after reconstitution, are reported in Table S1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By employing a rodent model of diet-induced obesity and metabolic syndrome, the authors demonstrated the ability of carnosinol to dose-dependently attenuate 4-hydroxynonenal adduct formation in liver and skeletal muscle, while simultaneously mitigating inflammation, dyslipidemia, insulin resistance, and steatohepatitis. As described by Grasso et al [ 136 ], alternative approaches to increase carnosine delivery and its bioavailability include the use of carnosine derivatives [ 137 , 138 , 139 ]; vesicular systems (nanoliposomes, niosomes, and polymerosomes) [ 140 , 141 , 142 , 143 ]; and nanoparticulate systems [ 144 , 145 , 146 , 147 ]. The currently “under-used” intranasal administration route might also represent an innovative approach, since it can purportedly bypass the BBB and first-pass metabolism [ 148 , 149 ]; the vasodilatory activity of carnosine [ 150 ] also makes this endogenous dipeptide an attractive candidate for this kind of delivery.…”
Section: In Vivo Preclinical Studies: Administration Route Dosage Tre...mentioning
confidence: 99%